Representation of Indigenous Peoples in the Education Curriculum in Norway and Alberta, Canada: A Postcolonial Analysis - Segarra, Eimi Segarra, 1990- (2019)
Native Peoples have historically populated several regions in the Arctic. Besides their similar lifestyles, these communities have experienced different situations that have shaped the divergent socio-cultural features that define their status nowadays. This way, the interaction with different civilisations has shaped their present agency. Indigenous Peoples in Norway are known as Sami. They live as well in Sweden, Finland and the peninsula of Kola in Russia. In Alberta, Canada, Aboriginal Peoples constitute three main groups: Inuit, Métis, and First Nations. The aim of this paper is to report how these Indigenous groups are represented in the current national curriculum for education in Norway and in the provincial curriculum for education in Alberta. The competence aims defined for both official documents were searched and the topics that address Indigenous Peoples’ issues were classified and analysed within the theoretical framework of decolonisation. The results obtained may serve as a source for reference in future reforms of the education curricula in the task of turning the education system into an inclusive space that promotes equal opportunities for all children.